The Median Effective Concentration (EC50) of Epidural Ropivacaine With Different Doses of Oxycodone During Limb Surgery in Elderly Patients - Xie, Kai; Wang, Yu-long; Teng, Wen-bin; He, Rui; Li, Yu-hong; Huang, Su-qin (Frontiers in Medicine, 2022)
Background: Oxycodone can be used both intravenously and epidurally in elderly patients because of its strong analgesic effect and more slight respiratory inhibition compared with by other opioids at the same effect. In this study, we determined the median effective concentration (EC50) of epidural ropivacaine required for great saphenous vein surgery in elderly patients in order to describe its pharmacodynamic interaction with oxycodone. Methods: One hundred forty-one elderly patients scheduled for high ligation and stripping of the great saphenous vein surgery were allocated into three groups in a randomized, double-blinded manner as follows: Q2.5 group (2.5 mg oxycodone), Q5.0 group (5.0 mg oxycodone) and C group (normal saline). Anesthesia, was achieved with epidural ropivacaine and oxycodone. The EC50 of ropivacaine for surgery with different doses of oxycodone was adjusted by using an up-and-down sequential methods with an adjacent concentration gradient at a factor of 0.9 to inhibit analgesia. Anaesthesia associated adverse events and recovery, characteristics were also recorded. Results: The EC50 of ropivacaine for the great saphenous vein surgery in elderly patients was 0.399% (95% CI, 0.371% to 0.430%) in the Q2.5 group, 0.396% (95% CI, 0.355% to 0.441%) in the Q5.0 group, and 0.487% (95% CI, 0.510% to 0.465%) in the C group respectively (P < 0.05). Specially, the EC50 of ropivacaine in the Q2.5 and Q5.0 groups was lower than that in the C group (P < 0.01), But the difference between the Q2.5 group and the Q5.0 group was not significant (P > 0.05). There was no significant difference in the Bromage score from the motor block examination, hear rate (HR) or mean arterial pressure (MAP) at each observation time point after epidural administration among the three groups (P > 0.05). No serious adverse reactions occurred in any of the three groups. Conclusion: Oxycodone combined with ropivacaine epidural anaesthesia can reduce the EC50 of ropivacaine required for elderly patients undergoing the great saphenous vein surgery. There was no significant difference in anaesthesia associated adverse events among the three groups. The recommended dose of oxycodone is 2.5 mg.